2010
DOI: 10.1126/science.1184429
|View full text |Cite
|
Sign up to set email alerts
|

Shaping Development of Autophagy Inhibitors with the Structure of the Lipid Kinase Vps34

Abstract: Phosphoinositide 3-kinases (PI3Ks) are lipid kinases with diverse roles in health and disease. The primordial PI3K, Vps34, is present in all eukaryotes and has essential roles in autophagy, membrane trafficking, and cell signaling. We solved the crystal structure of Vps34 at 2.9 angstrom resolution, which revealed a constricted adenine-binding pocket, suggesting the reason that specific inhibitors of this class of PI3K have proven elusive. Both the phosphoinositide-binding loop and the carboxyl-terminal helix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
231
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(243 citation statements)
references
References 28 publications
12
231
0
Order By: Relevance
“…This compound has been shown to be specific over PI3K kinases (10 fold more potent against PI4KIIIβ relative to p110α, and >100 fold more potent against PI4KIIIβ compared with all other class I and class III PI3K isoforms). Comparing the structure of PI4KIIIβ bound to BQR695 compared with structures of different PI3K inhibitor structures33, 34, 35, 36 reveals the molecular basis for this specificity. PI4KIIIβ has a larger binding pocket to accommodate the glycyl methyl amide group compared to the class I and class III PI3Ks.…”
Section: Resultsmentioning
confidence: 99%
“…This compound has been shown to be specific over PI3K kinases (10 fold more potent against PI4KIIIβ relative to p110α, and >100 fold more potent against PI4KIIIβ compared with all other class I and class III PI3K isoforms). Comparing the structure of PI4KIIIβ bound to BQR695 compared with structures of different PI3K inhibitor structures33, 34, 35, 36 reveals the molecular basis for this specificity. PI4KIIIβ has a larger binding pocket to accommodate the glycyl methyl amide group compared to the class I and class III PI3Ks.…”
Section: Resultsmentioning
confidence: 99%
“…The C2 domain does not affect the catalytic activity of the kinase and is thought to be involved in protein-protein interactions. The crystal structure of Vps34 lacking the C2 domain has been determined [172]. Vps34 has a highly ordered phosphatidylinositol-binding loop located in its catalytic domain, while the corresponding activation loop that is critical in substrate recognition in phosphoinositide 3-kinases is largely disordered.…”
Section: The Ptdins3k Complexesmentioning
confidence: 99%
“…[183][184][185][186] An early study resolved the molecular structure of PIK3C3, and revealed that PIK3C3 has a smaller and more rigid ATP binding pocket than that of PIK3CG, which restricts the binding of classical PI3K inhibitors. 187 This molecular dissection of PIK3C3 paved the way for the subsequent development of novel inhibitors that fit well within the PIK3C3 ATP cavity. A number of recent studies reported new PIK3C3 inhibitors, including VPS34-IN1, 184 Compound 31 (a tetrahydropyrimidopyrimidinone derivative), 186 PIK-III, 185 and SAR405; 183 among them, Compound 31 and SAR405 exhibit the highest potency (IC 50 PIK3C3 equals 2 nM and 1.2 nM, respectively) and favorable selectivity toward PIK3C3.…”
Section: Ptdins3k and Pi3k Inhibitors And Their Application In Autophmentioning
confidence: 99%